STUDY OF MAKING FRUIT LEATHER FROM APPLE MANGROVE ( Sonneratia caseolaris) AND PAPAYA ( Carica papaya L.) - arti, buni; lestari, retno budi; raharjo, dwi (Jurnal Sains Pertanian Equator, 2014)
THIS STUDY AIMS TO GET THE FORMULA FRUIT LEATHER FROM APPLE MANGROVE AND PAPAYA WITH THE BEST FISIKOKIMIA AND SENSORIES WHICH CAN BE ACCEPTED. THIS STUDY USING COMPLETE RANDOMIZED DESIGN (CRD) WITH 1 FACTOR THAT IS COMPARISON OF APPLE MANGROVE AND PAPAYA PER 1 LITRE WATER WITH 6 TREATMENTS WITH 4 REPLICATIONS. THE COMPARISON ARE 500G, 400G, 300G, 200G, 100G AND 0G OF APPLE MANGROVE WITH EACH PAPAYA 0G, 100G, 200G, 300G, 400G AND 500G. THE OBSERVATION VARIABLES ARE VITAMIN C, PH, ACID OF TOTAL, MOISTURE CONTENT, AND THE SENSORIES, IF TREATMENT HAVE AN EFFECT ON THE REALITY CONTINUED WITH THE TUKEY 5%. THE SENSORI TEST USED KRUSKAL-WALLIS METHOD AFTER THAT TO GET THE BEST TREATMENT OF TEST MAKE AN EFEKTIVINNES INDEX. THE RESULT SHOWS THAT THE LEVEL OF COMPARISON OF APPLE MANGROVE AND PAPAYA HAVE AN EFFECT ON THE VITAMIN C, TOTAL OF ACID, PH, MOISTURE CONTENT , COLOUR, TASTE, TEKSTUR AND AROMA, BUT HAVEN"™T AN EFFECT ON LIKED OF FRUIT LEATHER. FRUIT LEATHER WITH THE COMPARISON 300G APPLE MANGROVE : 200G PAPAYA HAS THE CHARACTERISTIC OF THE BEST FISIKOKIMIA AND SENSORI WITH VITAMIN C 8,14 MG / 100G, TOTAL OF ACID 1,99, PH 3,41, 24,03% MOISTURE CONTENT, COLOUR 3,48 ( NUTBROWN), AROMA 4,00 ( AROMA OF APPLE MANGROVE A LITTLE PAPAYA), TASTE 4,24 ( SWEET RATHER SOUR), TEKSTUR 3,64 ( FLEXING STICKY), AND LIKED 3,44 ( RATHER LIKE).